1986
DOI: 10.1128/mcb.6.11.4031
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of the promoter sequence in the J-chain gene is regulated by chromatin changes during B-cell differentiation.

Abstract: The gene for the immunoglobulin M (IgM)-polymerizing protein, the J chain, is activated when the mature B cell is triggered to secrete pentamer IgM. Activation of the gene was found to be associated with chromatin changes in a 240-base-pair region at the 5' end of the gene. Analyses of lymphoid lines showed that the 5' region was resistant to nuclease digestion at the immature B-cell stage; it became slightly more accessible in mature B cells and cells at an early stage in the IgM response and then displayed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…For these experiments, a reference plasmid was constructed from pCAT3M by inserting 1.24 kb of 5' J-chain sequence in the polylinker upstream of the CAT gene and 1.0 kb ofu heavy-chain enhancer sequence (19) at a BamHI site downstream. The J-chain insert spanned base pairs -1150 to +88 and included the region (-170 to +88) that becomes DNase I hypersensitive upon transcription (14). The translational start site encoded within the J-chain insert was altered by site-specific mutagenesis to ensure correct initiation of CAT translation.…”
Section: Identification Of a Major Control Region In The 5' Flankingmentioning
confidence: 99%
See 1 more Smart Citation
“…For these experiments, a reference plasmid was constructed from pCAT3M by inserting 1.24 kb of 5' J-chain sequence in the polylinker upstream of the CAT gene and 1.0 kb ofu heavy-chain enhancer sequence (19) at a BamHI site downstream. The J-chain insert spanned base pairs -1150 to +88 and included the region (-170 to +88) that becomes DNase I hypersensitive upon transcription (14). The translational start site encoded within the J-chain insert was altered by site-specific mutagenesis to ensure correct initiation of CAT translation.…”
Section: Identification Of a Major Control Region In The 5' Flankingmentioning
confidence: 99%
“…A single nuclease hypersensitive site is coinduced with J-chain gene expression either in normal B lymphocytes stimulated with mitogen or in BCL1 cells stimulated with recombinant IL-2 (14). This finding suggested that the lymphokine signal alters the 5' structure of the J-chain gene to allow access of the transcriptional machinery.…”
mentioning
confidence: 99%
“…A few clues to the mechanisms involved have been obtained in the case of J chain gene activation. Transcription of the gene has been shown to correlate with the development of a 5' hypersensitive site and a change in protein binding to that region (9,36). In contrast, essentially nothing is known ofthe events that regulate proliferation.…”
Section: In a Primary Immune Response A Resting B Lymphocyte Ismentioning
confidence: 99%
“…For efficient J chain transcription to occur, activation signals from both the B cell receptor and the interleukin-2 (IL-2) 1 or IL-5 receptors are needed. Correlating with IL-2/IL-5 induced gene transcription is the appearance of a DNase I-hypersensitive site (bp Ϫ170 to ϩ88) on the J chain promoter of activated B cells (2,3). The full activity of the J chain promoter is contained within this hypersensitive region, as has been shown using 5Ј deletion mutants in a CAT reporter system (4).…”
mentioning
confidence: 97%